PROBLEM BASED LEARNING: ADAPTING MODEL OF MONITORING AND ASSESSMENT TOWARDS CHANGING TO STUDENT CENTERED LEARNING - Masek, Alias; Yamin, Sulaiman (Journal of Technical Education and Training, 2010)
Exam oriented system has long time been practiced whether in the school or at higher educational level. It is common to see that students learn to rote memorization as preparation to pass in the examination. As consequences, the graduates’ ability to apply knowledge in the workplace becomes an issue to be debated. This has led to the loud calls for the new authentic learning environment that may increase students’ ability to apply knowledge, skills and at the same time promoting students’ with higher order thinking levels such as problem solving and critical thinking skills. Within this, the need on educational revamp is seem crucial, and this should be done from the grass root levels. Therefore, student centered learning using Problem Based Learning (PBL) approach is suggested to be introduced in integrated living skills subject. The model will be designed to focus on monitoring and assessment methods in fostering student continuous development in three domain areas of knowledge, technical and personal skills. Moreover, this method is believed to be able to incorporate lifelong learning and self directed learning skills that helps student to sustain in our educational system. Thus, the study aims to look into the possible ways of adapting PBL monitoring and assessment methods into existing practices in lifelong learning settings in TVET.